COURAGE AND FEAR IN THE CONTEXT OF OPPOSITION OF HUMAN ACTIVITY AND INACTIVITY: EXISTENTIAL ASPECT - Dmytro Yu. Snitko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the article is to analyse fear and courage in the history of philosophy in the context of opposi-tion of human activity and inactivity that may lead to a profound understanding of the essence, causes and existen-tial aspects of human activity and inactivity. The implementation of the objective assumes the solution of the follow-ing tasks: analysis of philosophical interpretation of fear and courage; investigation of the relationship of fear and courage with active and passive forms of human being; revelation of existential dialectic of human activity and inac-tivity through the opposition of fear and courage. Methodology. The application of phenomenological approach and other methods of existential philosophy enabled to discover the importance of fear and courage for human existence. Significant contribution to the importance of the investigation of the fear-courage opposition in the context of hu-man activity and inactivity was made by M. Heidegger who pointed to the main modes of human being - «authen-tic» and «inauthentic» in the context of human activity and passivity. The application of hermeneutic method made possible the reconstruction of the reflection of fear-courage opposition in the history of philosophy. Scientific nov-elty. For the first time the analysis of the fear-courage opposition in the context of human activity and inactivity was carried out. Due to the analysis the fundamental existential character of the fear and courage opposition and its es-sential relationship with active and passive forms of human being were justified. Conclusions. In the course of this research it was found out that fear is closely connected with passive modes of human being. If classical philosophy placed emphasis on courage and associated fear with human mind and conscious decision, non-classical philosophy of the XIX century and existentialism focused on existential and ontological character of fear, its fundamental mean-ing. These aspects of fear and courage (relation with the mind and ontological character) do not contradict each oth-er, but represent different dimensions of human being – freedom and loneliness in the world. Thus, the opposition of fear and courage has ontological and existential aspects, dialectical character and is closely connected with active and passive modes of human being.